Kajian Risiko Aflatoksin M1 dalam Produk Formula untuk Bayi dan Anak Usia 0-36 Bulan - Yeni Restiani; Lilis Nuraida; Hanifah Nuryani Lioe (Institut Pertanian Bogor, 2020)
Aflatoxin M1 (AFM1) is a carcinogenic compound found in milk-based products including infant and young children formula. The aim of this study was to determine the risk characterization of infants and young children to AFM1 through the consumption of formula products. For this purpose, the Estimated Daily Intake (EDI) for infants and young children was calculated by multiplying AFM1 concentration in 44 infant formulas, 53 advanced infant formulas, and 16 growing up formulas with consumption data. The concentration of AFM1 in these formula products were retrieved from food registration in Indonesian FDA from January 2015-June 2018. The average concentration of AFM1 in infant formula, advanced infant formulas, and growing up formula (lower bound-upper bound) were 0.0226-0.0335; 0.0418-0.0510; and 0.0038-0.0123 ng/g, respectively. The average EDI of AFM1 for infants and young children aged 0-6 months, 6-12 months, and 1-3 years based on individual consumption were 0.260-0.386, 0.282-0.343, 0.029-0.092 ng/kg body weight (BW)/day. The average EDI of AFM1 for infants and young children aged 0-6 months, 6-12 months, and 1-3 years based on the recommended consumption by food producer (lower bound-upper bound) were 0.403-0.598; 0.663-0.809; 0.031-0.098 ng/kgBW/day. The average hazard index (HI) values for infants aged 0-6 months and 6-12 months (lower bound-upper bound) were greater than 1 (one), i.e., 1.94-2.88 and 3.20-3.90, which indicates there is a health risk. However hazard index value for young children aged 1-3 years (lower bound-upper bound) were less than 1 (one), i.e., 0.15-0.47, which indicates a lower health risk. Keywords: advanced infant formula, aflatoxin M1, growing up formula, hazard index, infant formula